Meaningful social and economic inclusion through small business enterprise models of employment for adults with intellectual disability - Thoresen, S.; Thomson, Allyson; Jackson, R.; Cocks, Errol (IOS Press, 2018)
© 2018-IOS Press and the authors. All rights reserved. BACKGROUND: People with intellectual disability and high or very high support needs face systemic economic and social exclusion. Small business enterprise (SBE) models of employment focusing on adults with intellectual disability have emerged relatively recently, predominantly developed by parents. These are highly individualised, person-centred, and are built around the skills, strengths, and interests of the focal person. SBEs draw on a range of funding sources and paid and unpaid supports are instrumental in their development and continuation. OBJECTIVE: To explore the utility of SBE as an emerging employment pathway to economic and social inclusion for adults with intellectual disability. RESULTS: Four case studies describe a range of strategies to develop and maintain SBEs to create meaningful economic and social inclusion. They illustrate different supports used in establishing and continuing these arrangements, and issues related to safeguarding and sustainability. CONCLUSION: There is a dearth of empirical studies of SBE for people with intellectual disability who have high or very high support needs. Further work to develop and operationalise an SBE quality framework needs to account for the differences between the start-up and continuation stages, emphasising sustainability.